The reporting of pilot and feasibility studies in the top dental specialty journals is suboptimal - Mohammed I. U. Khan; Hartirath K. Brar; Cynthia Y. Sun; Rebecca He; Hussein A. El-Khechen; Katie Mellor; Lehana Thabane; Carlos Quiñonez (Pilot and Feasibility Studies, 2022)
Abstract Background Pilot and feasibility studies (PAFS) are smaller investigations seeking to assess the feasibility of conducting a larger more definitive study. In late 2016, the CONSORT statement was extended to disseminate good practices for reporting of randomized pilot and feasibility trials. In this quality assurance review, we assessed whether PAFS in the top dental speciality journals adhere to good practices of conduct and reporting, by prioritizing assessment of feasibility and stating pre-defined progression criteria to inform the decision to pursue funding for a larger trial. Methods With the help of a librarian, we searched MEDLINE and EMBASE from 2017 to 2020, inclusive, for PAFS in the top 3 journals from each of the 10 dental specialties. We collected data on methodological and general characteristics of the studies, their objectives, and reporting of items recommended in the CONSORT extension. Results Of the 111 trials included, 51.4% (95% CI 41.7–61.0%) stated some indication of intent to assess feasibility while zero reported progression criteria; 74.8% (95% CI 65.6–82.5%) of trials used the terms “pilot” or “feasibility” in their titles and 82.9% (95% CI 74.6–89.4%) of studies stated there is a need for a future trial, but only 9.0% (95% CI 4.4–15.9%) stated intent to proceed to one. Most of the studies, 53.2% (95% CI 43.4–62.7%), reported hypothesis testing without cautioning readers on the generalizability of the results. Studies that used the terms “pilot” or “feasibility” in their title were less likely to have feasibility objectives, compared to trials that did not, with an odds ratio (OR) of 0.310 (95% CI 0.103–0.930; p = 0.037). Compared to trials that did not conduct hypothesis testing, trials that conducted hypothesis testing were significantly less likely to assess feasibility, among them, trials that cautioned readers on the generalizability of their results had an OR of 0.038 (95% CI 0.005–0.264; p < 0.001) and trials that did not caution readers on the generalizability of their results had an OR of 0.043 (95% CI 0.008–0.238; p = 0.001). Conclusion Many PAFS in dentistry are not conducted with the intent of assessing feasibility, nor do they state progression criteria, and few report intent to proceed to a future trial. Misconceptions about PAFS can lead to them being poorly conducted and reported, which has economic and ethical implications. Research ethics boards, funding agencies, and journals need to raise their standards for the conduct and reporting of PAFS, and resources should be developed to address misconceptions and help guide researchers on the best practices for their conduct and reporting.